PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TIPE THINK PAIR SHARE TERHADAP KARAKTER MANDIRI KELAS VII PADA PEMBELAJARAN PANCASILA DAN KEWARGANEGARAAN DI MTS NEGERI 2 KISARAN - Triya Anggraini; Hapni Laila Siregar; Fazli Racham; Surya Dharma; Jamaludin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Think Pair Share Cooperative Learning Model on the Independent Character of Class VII in Pancasila and Citizenship Education Learning at MTs Negeri 2 Kisaran. This type of research uses a quantitative approach to determine the causal relationship between the independent variable (Thik Pair Share Cooperative Learning Model) and the dependent variable (Independent Character), a quasi-experimental method (Quasi Experiment) with a nonequivalent control group design. This study uses questionnaire data collection techniques, observation and documentation. This study was conducted at MTs Negeri 2 Kisaran. The population in the study were students of class VII MTs Negeri 2 Kisaran. The samples were students of class VII-G and VII-H. The data found were analyzed statistically with the t test, then normality test, homogeneity test, hypothesis test and Mann-Whitney test were carried out. The results showed that the Think Pair Share cooperative learning model had a positive and significant effect on the independent character of class VII MTs Negeri 2 Kisaran. This is proven by the results of the Independent Sample t-test which obtained a t-value of 23.512 with a significance value of 0.000 <0.05. In addition, there is a significant difference in independent character between students who learn using the Think Pair Share cooperative learning model and students who learn using conventional learning, with a t-value of 7.754 and a significance value of 0.000 <0.05. The results of observations of student activities also show a percentage of 93.3% with a very good category. Thus, the Think Pair Share cooperative learning model is proven to be more effective in forming students' independent character compared to conventional learning.